Are community-based nurse-led self-management support interventions effective in chronic patients? Results of a systematic review and meta-analysis. - Azzurra Massimi; Corrado De Vito; Ilaria Brufola; Alice Corsaro; Carolina Marzuillo; Giuseppe Migliara; Maria Luisa Rega; Walter Ricciardi; Paolo Villari; Gianfranco Damiani (PLoS ONE)
The expansion of primary care and community-based service delivery systems is intended to meet emerging needs, reduce the costs of hospital-based ambulatory care and prevent avoidable hospital use by the provision of more appropriate care. Great emphasis has been placed on the role of self-management in the complex process of care of patient with long-term conditions. Several studies have determined that nurses, among the health professionals, are more recommended to promote health and deliver preventive programs within the primary care context. The aim of this systematic review and meta-analysis is to assess the efficacy of the nurse-led self-management support versus usual care evaluating patient outcomes in chronic care community programs. Systematic review was carried out in MEDLINE, CINAHL, Scopus and Web of Science including RCTs of nurse-led self-management support interventions performed to improve observer reported outcomes (OROs) and patients reported outcomes (PROs), with any method of communication exchange or education in a community setting on patients >18 years of age with a diagnosis of chronic diseases or multi-morbidity. Of the 7,279 papers initially retrieved, 29 met the inclusion criteria. Meta-analyses on systolic (SBP) and diastolic (DBP) blood pressure reduction (10 studies-3,881 patients) and HbA1c reduction (7 studies-2,669 patients) were carried-out. The pooled MD were: SBP -3.04 (95% CI -5.01--1.06), DBP -1.42 (95% CI -1.42--0.49) and HbA1c -0.15 (95% CI -0.32-0.01) in favor of the experimental groups. Meta-analyses of subgroups showed, among others, a statistically significant effect if the interventions were delivered to patients with diabetes (SBP) or CVD (DBP), if the nurses were specifically trained, if the studies had a sample size higher than 200 patients and if the allocation concealment was not clearly defined. Effects on other OROs and PROs as well as quality of life remain inconclusive.